Explorations; T1: Student book - Linda Lee (Oxford Univ. Press, 2000)
The book contains eight units which integrate grammar, speaking, listening, reading, and writing around engaging, interesting topics. The Grammar Guide and Vocabulary Workshop sections in the back of the book can be used to support and expan each unit.